2017
DOI: 10.3390/ijms18040782
|View full text |Cite
|
Sign up to set email alerts
|

Alleviation of Ultraviolet B-Induced Photodamage by Coffea arabica Extract in Human Skin Fibroblasts and Hairless Mouse Skin

Abstract: Coffea arabica extract (CAE) containing 48.3 ± 0.4 mg/g of chlorogenic acid and a trace amount of caffeic acid was found to alleviate photoaging activity in human skin fibroblasts. In this study, polyphenol-rich CAE was investigated for its antioxidant and antiinflammatory properties, as well as for its capability to alleviate ultraviolet B (UVB)-induced photodamage in BALB/c hairless mice. The results indicated that 500 μg/mL of CAE exhibited a reducing power of 94.7%, ferrous ion chelating activity of 46.4%,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 55 publications
1
39
0
7
Order By: Relevance
“…Th cells were thought to lose this regulatory function owing to a reduction in Tregs; this would result in overexpression of Th2 cells and increased IL-6 levels, thereby. Increased IL-6 induces the degradation of collagen in the skin [38, 39]. Therefore, in stressed arthritic mice, this mechanism may have contributed to the deterioration of dry skin.…”
Section: Discussionmentioning
confidence: 99%
“…Th cells were thought to lose this regulatory function owing to a reduction in Tregs; this would result in overexpression of Th2 cells and increased IL-6 levels, thereby. Increased IL-6 induces the degradation of collagen in the skin [38, 39]. Therefore, in stressed arthritic mice, this mechanism may have contributed to the deterioration of dry skin.…”
Section: Discussionmentioning
confidence: 99%
“…Also, chronic exposure of the skin to UV radiation stimulates mitogen‐activated protein kinase signaling pathway resulting in the induction of MMPs, such as MMP‐1, also known as interstitial collagenase, which is responsible for the degradation of dermal type 1 collagen that is the most abundant structural protein in the dermis (Jung, Lee, Lee, & Cho, ). The topical application of natural products with high antioxidant and anti‐inflammatory activity may ameliorate UV‐induced photodamage (Wu et al, ). In this study, we also found that topical administration of DLE, CLE, or DLE/CLE prevented UVB‐induced skin damage, epidermal hyperplasia, and collagen degradation in the skin of SHK‐1 mice.…”
Section: Discussionmentioning
confidence: 99%
“…S1 and , Tables S1 and ) interstitial collagenase, which is responsible for the degradation of dermal type 1 collagen that is the most abundant structural protein in the dermis (Jung, Lee, Lee, & Cho, 2016). The topical application of natural products with high antioxidant and anti-inflammatory activity may ameliorate UV-induced photodamage (Wu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…After the cells were treated for 24 h, the effect of G6 on cell viability was monitored by the MTT assay. MTT solution (5 mg/mL in PBS buffer) was added and incubated for 4 h. Then, the medium was removed and replaced with DMSO to dissolve the potassium salt and the absorbance was measured at 570 nm [70,71].…”
Section: Mtt Assaymentioning
confidence: 99%